2016
DOI: 10.4236/oje.2016.67042
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Levels of Nitrogen on Yield and Yield Components of Rainfed Wheat in Two Regions of North Khorasan

Abstract: To study the effects of different levels of nitrogen fertilizer on yield and yield components of cultivars of rainfed wheat a study was done in the crop year 2012-2013 as factorial in a randomized complete block design with 3 replications, in 2 research stations of Kohne Kand city in Bojnord and Shirvan dryland research station. The treatments of study contain cultivars of wheat in 4 levels (Rasad, Sabalan, Cross Sabalan and Azar 2) and 4 levels of nitrogen fertilizer (75, 50, 25 and 0 kilograms nitrogen per h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Also, increased nitrogen fertilization led to increase production of wheat yield due to strong response to additions of nitrogen, which is regarded as the main element in the construction of amino acids, proteins and enters in many physiological processes in plant. These results are in harmony with those recorded by Abd El-Lattief (2013), Abou-Keriasha & Essa (2014), Bavar et al (2016) and El-Temsah (2017).…”
Section: Effect Of Nitrogen Levelssupporting
confidence: 91%
“…Also, increased nitrogen fertilization led to increase production of wheat yield due to strong response to additions of nitrogen, which is regarded as the main element in the construction of amino acids, proteins and enters in many physiological processes in plant. These results are in harmony with those recorded by Abd El-Lattief (2013), Abou-Keriasha & Essa (2014), Bavar et al (2016) and El-Temsah (2017).…”
Section: Effect Of Nitrogen Levelssupporting
confidence: 91%
“…Nitrogen is a primary element of proteins, Rubisco, and chlorophyll, which influence many critical processes including photosynthesis and root development (Abid et al., 2016; Shangguan, Shao, Ren, Zhang, & Xue, 2004). Efficient N application increases photosynthesis rate, leaf area index, and radiation use efficiency, optimizing wheat yield and quality (Abid et al., 2016; Bavar, Abad, & Noormohamadi, 2016). Nonetheless, several studies have shown poor N fertilizer recovery in many cereal cropping systems, resulting in 50–60% of applied N fertilizer not being effectively utilized by the crop (Gupta & Khosla, 2012; Peng et al., 2010; Ruisi et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, assimilates are produced to strengthen spikelet developments. Thus, a more incredible spikelets/spike was formed (23). The nitrogen fertilizer application was increasing in the share of reproductive organs, including the number of spikelets per spike (24).…”
Section: Spikelets/spikementioning
confidence: 99%